Mathematical Modelling of Nitric Oxide/Cyclic GMP/Cyclic AMP Signalling in Platelets - Kleppe, Rune (Int J Mol Sci, 2018)
Platelet activation contributes to normal haemostasis but also to pathologic conditions like stroke and cardiac infarction. Signalling by cGMP and cAMP inhibit platelet activation and are therefore attractive targets for thrombosis prevention. However, extensive cross-talk between the cGMP and cAMP signalling pathways in multiple tissues complicates the selective targeting of their activities. We have used mathematical modelling based on experimental data from the literature to quantify the steady state behaviour of nitric oxide (NO)/cGMP/cAMP signalling in platelets. The analysis provides an assessment of NO-induced cGMP synthesis and PKG activation as well as cGMP-mediated cAMP and PKA activation though modulation of phosphodiesterase (PDE2 and 3) activities. Both one- and two-compartment models of platelet cyclic nucleotide signalling are presented. The models provide new insight for understanding how NO signalling to cGMP and indirectly cAMP, can inhibit platelet shape-change, the initial step of platelet activation. Only the two-compartment models could account for the experimental observation that NO-mediated PKA activation can occur when the bulk platelet cAMP level is unchanged. The models revealed also a potential for hierarchical interplay between the different platelet phosphodiesterases. Specifically, the models predict, unexpectedly, a strong effect of pharmacological inhibitors of cGMP-specific PDE5 on the cGMP/cAMP cross-talk. This may explain the successful use of weak PDE5-inhibitors, such as dipyridamole, in anti-platelet therapy. In conclusion, increased NO signalling or PDE5 inhibition are attractive ways of increasing cGMP-cAMP cross-talk selectively in platelets.